Cora Wilson Stewart and Kentucky's moonlight schools : fighting for literacy in America - Baldwin, Yvonne Honeycutt, 1947- (University Press of Kentucky, 2006)
Cora Wilson Stewart (1875-1958) was an elementary school teacher and county school superintendent in eastern Kentucky who, in the fall of 1911, decided to open the classrooms in her district to adult pupils. Convinced that education could eliminate the poverty that plagued the region, she founded the Moonlight School movement, ultimately designed to combat illiteracy. The movement's motto, "Each one teach one," characterized education as the responsibility of every literate citizen. Stewart's Moonlight Schools caught on quickly, and when the state legislature created the Kentucky Illiteracy Co.